The Structure and Function of the World Customs Organization - Carsten Weerth (Global Trade and Customs Journal, 2009)
The World Customs Organization (WCO, Organization Mondiale des Dounaes, OMD) is an intergovernmental organization of more than 170 Member States. It is of tremendous importance for the simplification of international trade and customs procedures; however, its modes of action and decision-making processes have been very secretive for a very long time. Only in very recent years the WCO has decided to open up (in particular by help of the internet) and it now explains its ways of action. This paper gives an overview of the WCO structures, committees, and functions.
Additional information: Self-archiving of author's post-print (accepted paper) for scientific use only on personal page in RePec (e.g. https://authors.repec.org) according to publishers policies as documented on SHERPA/ROMEO database under URL: http://www.sherpa.ac.uk/romeo/issn/1569-755X/en//. Copyright-holder is Kluwer Law International.
Keywords: K33; F53; 330; Customs Law; World Customs Organization